Implications of a constitutional procedural codification in Colombia [Implicaciones de una codificación procesal constitucional para Colombia] (2019)
This paper analyses constitutional procedural law in Colombia. The existing debate regarding the codification of constitutional procedural law, along with its arguments for and against, is explained. It also studies the implications that this codification of constitutional procedural law may have on a State, specifically Colombia, regarding the reorganization of a constitutional jurisdic-tion, the role that judges must fulfill, the binding force of their decisions, and the relationship within the block of constitutionality and conventionality, pointing at the necessity to clearly design this codification upon the scope of those implications. © 2019, Universidad Nacional Autonoma de Mexico. All rights reserved.